The Impact of Coronavirus Disease 2019 on Plastic Surgery Training: The Resident Perspective - Kapila, Ayush K. (Plast Reconstr Surg Glob Open, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has led to marked changes in surgical training, including that of plastic surgery residents. We performed a survey to gain an insight into the self-reported current and future impact of COVID-19 on plastic surgery residents. METHODS: A 20-point questionnaire was designed by a panel of surgical trainees and trainers, which was filled in by Belgian plastic surgery residents and their international network of peers between 19 and 26 April 2020—week 6 of stringent Belgian lockdown measures. Questions covered the impact of COVID-19 on surgical activity, surgical training, and the future of training. RESULTS: Thirty-five of 38 plastic surgery residents in Belgium filled in the questionnaire, as did 51 of their international peers from 9 other countries. Decreased surgical activity of >75% was reported by 86% of Belgian trainees and by 73% of international colleagues. All consultations were stopped for 26% of Belgian trainees and 37% of international peers. Forty-six percents of Belgian trainees and 27% of international peers were reassigned to different departments. Eighty-five percent of all trainees felt surgical training had suffered, yet 54% of Belgian residents and 39% of international peers felt training should not be prolonged. Anxiety regarding the pandemic was present in 54% of Belgian residents and 69% of international colleagues. CONCLUSIONS: This is the first report, expressing the voice of a representative group of plastic surgery residents, showing a significant impact of COVID-19 on training and activity. A joint effort is needed to provide continued forms of education by virtual education and skills-based learning.